Relationship Between Gross Motor Function and Nutritional Status in Children with Cerebral Palsy attending a Tertiary Children’s Hospital of Nepal - Dhaubhadel, Suraj; Prajapati, Bina; Nepal, Deepeshwara (Journal of Nepal Paediatric Society, 2022)
Introduction: Malnutrition is a common problem in children with cerebral palsy and their management outcome is not satisfactory unless we address their nutritional aspect. The present study aims to find the relationship between gross motor function and nutritional status in these children by comparing the proportion of stunting, wasting and under-weight between the various levels of gross motor function. Methods: Our study was across- sectional study conducted on 82 cases of cerebral palsy between one to five years of age visiting Kanti Children’s Hospital, Kathmandu, Nepal from May 2017 to September 2018. Their level of gross motor function was ascertained by applying the Gross Motor Function Classification System (GMFCS) and anthropometry was done using standard methods. On the basis of their motor function, the children were divided into two categories: those with poorer motor function who had poor self-mobility even with assistance (GMFCS level 4 and 5) and those with better motor function who had self-mobility with various degrees of assistance (GMFCS level 1, 2 and 3). Wasting, stunting and under-weight were compared between the two categories and odds ratio with 95% confidence interval was estimated for malnutrition. Results: The children belonging to poorer motor function were more likely to be underweight (Odds ratio 3.41; CI 1.36-8.52; p-value 0.008) and stunted (Odds ratio 3.9; CI 1.47-10.53; p-value 0.048) than those with better motor function. Conclusions: Children with poorer motor function are more likely to develop malnutrition (Specially stunting) than those with better motor function indicating that chronic form of malnutrition is more common in these children.